Adoption of soil conservation through collective actions in Southwestern Uganda - Kalibwani, R.M.; Kakuru, M.; Kamugisha, R.; Twebaze, Jennifer; Hilman, E.; Tumuheirwe, H.; Tenywa, M.M.; Nyamwaro, Sospeter S.; Mugabo, J.; Buruchara, Robin Arani; Fatunbi, A.O.; Adekunle, A. (African Journals Online, 2017)
In developing countries, access to and use of renewable natural resources are essential for rural livelihoods to thrive. Hence, cooperation in the management of natural resources is increasingly an important strategy that can enhance long-term socio-ecological resilience. In most cases, collective actions have widely been recognised as an alternative institutional arrangement to centralised governance for the management of natural resources, but their success largely depends on factors that are specific to localities where they are implemented. In this study, factors that influence adoption and extent of adoption of natural resource conservation activities were identified using two case studies: Bubaare and Bufundi Innovation Platforms in Uganda. The drivers of adoption of community natural resource management strategies are analysed using an Ordered Logit Model while extent of adoption is analysed using a truncated regression model. The education level of a household head, membership in collective action group, and perception of plot slope and relevance of bye-laws were factors associated with likelihood of adoption. Value of livestock, membership in collective action group, access to credit and off-farm income were found to positively influence the level of investment. Thus, collective action increases opportunities for adoption; hence farmers should be supported to work collectively.